Prevalence and characteristics of gastrointestinal infections in men who have sex with men diagnosed with rectal chlamydia infection in the UK: an 'unlinked anonymous' cross-sectional study. (30th March 2017) - Hughes, Gwenda; Silalang, Panida; Were, John; Patel, Hemanti; Childs, Tristan; Alexander, Sarah; Duffell, Stephen; Saxon, Cara; Ison, Cathy; Mitchell, Holly; Field, Nigel; Jenkins, Claire
Abstract : Introduction: Gastrointestinal infections (GII) can cause serious ill health and morbidity. Although primarily transmitted through faecal contamination of food or water, transmission through sexual activity is well described, especially among men who have sex with men (MSM). Methods: We investigated the prevalence of GIIs among a convenience sample of MSM who were consecutively diagnosed with rectal Chlamydia trachomatis (CT) at 12 UK genitourinary medicine clinics during 10 weeks in 2012. Residual rectal swabs were coded, anonymised and tested for Shigella, Campylobacter, Salmonella, shiga toxin-producing Escherichia coli and enteroaggregative E. coli (EAEC) using a real-time PCR. Results were linked to respective coded and anonymised clinical and demographic data. Associations were investigated using Fisher's exact tests. Results: Of 444 specimens tested, overall GII prevalence was 8.6% (95% CI 6.3% to 11.6%): 1.8% (0.9% to 3.6%) tested positive for Shigella, 1.8% (0.9% to 3.6%) for Campylobacter and 5.2% (3.5% to 7.7%) for EAEC. No specimens tested positive for Salmonella or other diarrhoeagenic E. coli pathotypes. Among those with any GII, 14/30 were asymptomatic (2/7 with Shigella, 3/6 with Campylobacter and 9/17 with EAEC). Shigella prevalence was higher in MSM who were HIV-positive (4.7% (2.1% to 10.2%) vs 0.5%(0.1% to 3.2%) in HIV-negative MSM; p=0.01). Conclusions: In this small feasibility study, MSM with rectal CT appeared to be at appreciable risk of GII. Asymptomatic carriage may play a role in sexual transmission of GII.